Determination of Technopreneurship, Work Motivation, Digital Literacy on the Work Readiness of Information Technology Students - Yogi Irdes Putra; Ali Idrus; Firman; Sofyan (Jurnal Penelitian Pendidikan IPA, 2026)
The rapid advancement of digital technology has created both opportunities and challenges for Information Technology graduates, particularly regarding their work readiness in facing industry demands. This study aims to analyze the determinants of technopreneurship, work motivation, and digital literacy on the work readiness of Information Technology students in private universities in Jambi Province. Using a quantitative survey approach, data were collected from 307 active IT students selected through proportional random sampling. Data were gathered using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 4.1.14. The findings reveal that all three independent variables have a positive and significant effect on students' work readiness, with digital literacy emerging as the strongest determinant (β = 0.341, p < 0.05), followed by technopreneurship (β = 0.312, p < 0.05) and work motivation (β = 0.278, p < 0.05). The model's R² value of 0.67 indicates that 67% of the variance in work readiness is explained by the three predictors. These results highlight the critical role of integrating technopreneurship and digital literacy within higher education curricula to enhance graduate employability in the digital economy era. The practical implication emphasizes the need for project-based learning, startup incubators, and adaptive digital training programs. The originality of this research lies in its simultaneous examination of technopreneurship, work motivation, and digital literacy as predictors of IT students' work readiness within an Indonesian regional higher education context, an area rarely explored in prior studies